Highly singlet oxygen generative water-soluble coumarin substituted zinc(II) phthalocyanine photosensitizers for photodynamic therapy - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
New tetra-non-peripherally and peripherally ethyl butyrate or butanoic acid and their sodium salts bearing coumarin substituted zinc(II) phthalocyanine complexes have been synthesized and characterized for the first time. Butanoic acid bearing coumarin substituted zinc(II) phthalocyanine complexes and their sodium salts show excellent solubility in aqueous solution. Photophysical and photochemical properties of these phthalocyanines were investigated. General trends are described for photodegradation, fluorescence and singlet oxygen quantum yields as well as fluorescence lifetimes of these compounds. The value of singlet oxygen quantum yields ranged from 0.65 to 0.93 in phosphate-buffered saline + Triton X-100 solution indicating that they can produce singlet oxygen in high efficiency. This study also presented the synthesized water soluble zinc(II) phthalocyanines strongly bind to bovine serum albumin. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Coumarin (2H-1-benzopyran-2-one); Zinc; Water soluble; Photodynamic therapy; Singlet oxygen; PHOTOPHYSICAL PROPERTIES; PHOTOCHEMICAL PROPERTIES; OPTICAL-PROPERTIES; BEHAVIOR; SOLVENT